2005
DOI: 10.1111/j.1751-0813.2005.tb13090.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of wild waterfowl in the epidemiology of AI in Australia

Abstract: Dr Turner's correspondence (Aust Vet J82:713) requires further comments and clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In most outbreaks of AI in Australia, direct and indirect contact between wild waterfowl and poultry has been identified as an important introduction pathway for AI [ 20 ]. In at least two of the seven Australian outbreaks of HPAI, surface drinking water contaminated with waterfowl faeces was suspected to be the source of infection [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most outbreaks of AI in Australia, direct and indirect contact between wild waterfowl and poultry has been identified as an important introduction pathway for AI [ 20 ]. In at least two of the seven Australian outbreaks of HPAI, surface drinking water contaminated with waterfowl faeces was suspected to be the source of infection [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sampling in Australia (and worldwide) has targeted Anseriformes and Charadriiformes (Senne 2003;Arzey 2004aArzey , 2004bArzey , 2005Bunn 2004;Tracey et al 2004;Turner 2004;East et al 2008aEast et al , 2008bMcCallum et al 2008;Sims and Turner 2008;Hamilton et al 2009), despite LPAI viruses having been found to infect more than 100 host species, in 26 families, including many whose primary habitat is not aquatic . Indeed, the question yet to be addressed is which species are reservoirs or temporary hosts for these viruses in Australia.…”
Section: What Role Do Resident Birds Play In the Ecology And Epidemiomentioning
confidence: 99%
“…Although a shift in pathogenicity for avian influenza can occur rapidly (Brugh and Beck 1992, one or two passages;Arzey 2005), population size or density is likely to be important in determining the levels of prevalence, transmissibility and mutation rates for many viruses (e.g. rabbit haemorrhagic disease virus in rabbits (Calvete and Estrada 2000;Henzell et al 2002), brucellosis in bison (Dobson and Meagher 1996), Mycoplasma gallisepticum in house sparrows (Hochachka and Dhondt 2000)), including avian influenza (Bunn 2004;Turner 2004;Pfeiffer et al 2007;Snow et al 2007).…”
Section: Risk Profilesmentioning
confidence: 99%